1979
DOI: 10.2136/sssaj1979.03615995004300040024x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Availability in a Calcareous Soil After High Loading Rates of Animal Manure

Abstract: The fixing of phosphorus (P) added to calcareous soils is rapid but can be reduced by applying organic sources. The objectives of this study were to measure in the field the residual NaHCO3‐extractable P resulting from manure applications at high rates and to contrast the NaHCO3‐extractable P levels for manure vs. inorganic P fertilizers.When inorganic P was applied at 490 kg/ha for each of 2 years the NaHCO3‐extractable P was increased from 16 to 31 ppm at the 0‐ to 30‐cm depth. The application of 98 kg/ha of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…McCoy et al [8] found that biosolids (treated City wastes) P was four to seven times less available than triple super phosphate P. In contrast, other studies have suggested that P in organic amendments may be equally or more available than fertilizer P [9,10]. Therefore, this study was conducted to investigate the effects of cow manure, city wastes, chicken manure and TSP on the growth of corn and phytoavailability of phosphorus in soils.…”
Section: Introductionmentioning
confidence: 96%
“…McCoy et al [8] found that biosolids (treated City wastes) P was four to seven times less available than triple super phosphate P. In contrast, other studies have suggested that P in organic amendments may be equally or more available than fertilizer P [9,10]. Therefore, this study was conducted to investigate the effects of cow manure, city wastes, chicken manure and TSP on the growth of corn and phytoavailability of phosphorus in soils.…”
Section: Introductionmentioning
confidence: 96%
“…McCoy et al (1986) reported that biosolids P was four to seven times less available to plants compared to triple super phosphate. On the other hand, Tunney and Pommel (1987) reported that P in pig slurry was at least 90% as effective as fertilizer P because pig slurry contains 70 to 90% inorganic P. Other studies have suggested that manure P may be equally or more available than fertilizer P (Gale et al 2000;Meek et al 1979). A measure of the forms of P in soil amended with biosolids and manures, and how these forms change with time, can provide important information on how these amendments affect soil test P and plant available P.…”
mentioning
confidence: 99%
“…Consequently, different measurement procedures and limits are required to define solubility, mobility, and plant availability of P (Olsen et al, 1954). Inorganic P fixation in calcareous soils is relatively rapid whereas the rate and extent of fixation may be much slower or less extensive when P is added with organic matter or in an organic form (Meek et al, 1979).…”
mentioning
confidence: 99%
“…Utah calcareous soils that had received turkey and beef manures for two to four decades showed increased bicarbonate extractable ortho-and total-P (STP and STPt) concentrations to a depth of 2.1 m in most cases (James et al, 1996). A calcareous California soil that received 1336 kg P ha" with applied feedlot manure still contained 53 mg STP kg' in the surface 0.30 m after 6 yr (Meek et al, 1979). Higher manure rates increased surface soil STP concentrations to 237 mg kg-1 .…”
mentioning
confidence: 99%